PENGARUH MODEL PEMECAHAN MASALAH KREATIF TERHADAP KOMPETENSI BELAJAR FISIKA PESERTA DIDIK KELAS X SMA NEGERI 1 LUBUK ALUNG - Rizka Ariani; Djusmaini Djamas; Nurhayati Nurhayati (PILLAR OF PHYSICS EDUCATION, 2016)
One of the factors that lead to low learning outcomes of students is the poor ability of learners in solving physics problems.This problem-solving skills can be improved through learning using the Creative Problem Solving model. The purpose of this research was to investigate the effect of applying creative problem-solving model to study physics competency achievement of learners.Type of the research is quasi experimental study design by randomized control group only design, The research population includes all students of class X MIA that registered in the second semester of the academic year 2015/2016. Sampling technique was purposive sampling continued with cluster random sampling.  The research data is the grades of competence of knowledge, attitudes and skills of students.The research instrument was the ultimate test for measuring the competence of knowledge,observation sheets to measure competence of attitudes,performance assessment sheet to measure competence of skills. The research data analyzed by the equality test of two average and regression and correlation test. Equality test of two averages performed for the value of the learning outcomes of each competency of both class sample. Regression and correlation test performed to the value of learning outcomes of class knowledge experiment competence.Based on the analysis of data obtained by the average value for the experimental class and the control class in a row on the competence of knowledge is 83.47 and 78.16, on the competence of the attitude that is 87.04 and the average value for the experimental class and the control class in a row on the competence of skillis 88,7 and 83,3. Data for the competence of knowledge, attitudes and skills of both classes of samples normally distributed and have homogeneous variances, so performed test the equality of two average by t. From the calculation results obtained t value for competence and knowledge are 2.773 t table = 2.00; on the competence acquired attitude t ie 7.1911 and t table = 2.00; and the competence acquired skills t are 4.189 and t table = 2.00. The degree of correlation value of creative problem-solving model to value knowledge competency is moderate, and the influence of the model of 31.10%. So, the conclusion from this study is there a meaningful impact on the implementation of creative problem-solving model for the competence of students studying physics class X SMAN 1 Lubuk Alung received